Pengaruh Outdoor Learning Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun di TK IKI PTPN VII Musi Landas - Putri, Yecha Febrieanitha; Astuti, Mardiah; Zuhdiyah, Zuhdiyah; Fitri, Izza; Sastia (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study examines the influence of outdoor learning on the socio-emotional development of children aged 5–6 years at TK IKI PTPN VII Musi Landas. A quantitative one-group pretest–posttest design was employed with 14 purposively selected children who participated in structured outdoor learning sessions. Children’s socio-emotional development was assessed through systematic observation conducted before and after the intervention. The results indicate a significant improvement in socio-emotional development following outdoor learning activities (t_cal = 14.741, α = 0.05). Post-intervention observations revealed notable gains in empathy, cooperation, responsibility, independence, and emotional control. Outdoor settings provided children with authentic opportunities to interact with peers and the environment, encouraging social sensitivity, self-regulation, and confidence through active, contextual experiences. These findings suggest that outdoor learning can function as an effective pedagogical strategy to strengthen socio-emotional competencies in early childhood, complementing cognitive growth with meaningful social and emotional engagement. The study offers practical evidence for educators and schools to integrate well-designed outdoor activities into daily learning to support holistic child development.